2022
DOI: 10.2340/jrm.v54.882
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Robot-Assisted Training Versus Enhanced Upper Extremity Therapy on Upper and Lower Extremity for Stroke Survivors: A Multicentre Randomized Controlled Trial

Abstract: Objective: Robot-assisted neuro-rehabilitation therapy plays a central role in upper extremity recovery of stroke. Even though, the efficacy of robotic training on upper extremity is not yet well defined and scant attention has been devoted to its potential effect on lower extremity. In this paper, the aim was to compare efficacy on upper and lower extremities between robot-assisted training (RAT) and therapist-mediated enhanced upper extremity therapy (EUET).Methods: A  randomized clinical trial involving 172… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A significant improvement in the Barthel Index and ADLs was observed after the intervention, reflecting a higher level of independence after being released from hospital. Other studies analyzing the effect of RAT on stroke demonstrated improvement in the Barthel index or the Fugh-Meyer Scale [ 30 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant improvement in the Barthel Index and ADLs was observed after the intervention, reflecting a higher level of independence after being released from hospital. Other studies analyzing the effect of RAT on stroke demonstrated improvement in the Barthel index or the Fugh-Meyer Scale [ 30 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, it is a novel integrated treatment method for combining synergy-based FES and RAT interventions, based on integrated rehabilitation technologies and synergistic enhancement effects for improving the upper limb function after stroke. Previous studies examined individual components (e.g., CRP, FES, RAT) but have not combined them in an integrated method [ 4 , 20 , 29 ]. Second, the comprehensive intervention protocol will be evidence-based and rigorously developed based on the evidence, recommendations, theories and practice standards of the systematic review [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike synergy-based FES that activates weak muscles, robotic-assisted therapy (RAT) is another upper limb rehabilitation approach, which allows an intensive, high frequency repeat training in accordance with principles of motor learning[6, [19][20][21]. More importantly, so far, the RAT training system could design accurate movement trajectory that ts ADL as training target for drive optimal control strategies in real environments, such as reach-to-grasp (RTG).…”
Section: Introductionmentioning
confidence: 99%